Empowering Young High School Students Through The Preservation Of Traditional Health Therapy Tools As Local Wisdom Heritage - Nurhadi Santoso; Agus Wiyanto; Masri; Dian Kusumawati (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
Preserving local wisdom in the field of health, particularly traditional health therapy tools, has become a challenge in the era of modernisation due to the declining interest of the younger generation in learning about and applying them. This community service activity aims to empower senior high school students through education, practical training, and participatory empowerment so that they are able to understand, use, and preserve traditional health therapy tools as cultural heritage. The methods used include needs identification, educational socialisation, guided practical training, empowerment of students as agents of preservation, and periodic monitoring and evaluation. The results of the community service show an increase in students' knowledge, attitudes, and skills in using traditional therapy tools, as well as an increase in their enthusiasm to play an active role in preserving local wisdom. This activity also fostered students' awareness of cultural and health values based on local wisdom, while shaping the character of the younger generation to care about culture and community welfare. Thus, empowering students through community service can be an effective strategy for maintaining the sustainability of traditional health therapy tools and strengthening the nation's cultural identity.